2015
DOI: 10.5851/kosfa.2015.35.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antioxidant Activities of Hydrolysates of Domestic and Imported Skim Milk Powders Treated with Papain

Abstract: Milk proteins have many potential sequences within their primary structure, each with a specific biological activity. In this study, we compared and investigated the bioactivities of hydrolysates of the domestic (A, B) and imported (C, D) skim milk powders generated using papain digestion. MALDI-TOF analysis revealed that all milk powder proteins were intact, indicating no autolysis. Electrophoretic analysis of hydrolysates showed papain treatment caused degradation of milk proteins into peptides of various si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
(57 reference statements)
0
4
1
Order By: Relevance
“…The ABTS value of SBMP (Table 2) was lower compared to the reported 57% [87] and 75% RSA [88] values for SMP. Meanwhile, the DPPH value for SBMP (Table 2) was higher than that of (77-94%) WMP [89], (3.26%) buffalo milk powder [90] and (2.87%) cow milk powder [90].…”
Section: Antioxidant Properties Of Sbmpcontrasting
confidence: 55%
See 1 more Smart Citation
“…The ABTS value of SBMP (Table 2) was lower compared to the reported 57% [87] and 75% RSA [88] values for SMP. Meanwhile, the DPPH value for SBMP (Table 2) was higher than that of (77-94%) WMP [89], (3.26%) buffalo milk powder [90] and (2.87%) cow milk powder [90].…”
Section: Antioxidant Properties Of Sbmpcontrasting
confidence: 55%
“…The total phenolic compound content of SBMP ( Table 2 ) was higher than that of WMP (8.1–9.8 mg/L) [ 89 ], SMP (163.75–96.48 μM GE/L) [ 87 ], cow milk powder (0.49 mg GAE/g) and buffalo milk powder (3.26 mg GAE/g) [ 90 ]. The presence of phenolic compounds at high levels in cattle feed and the microbial activity in milk are liable for the presence of phenolic compounds in milk [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we suggested the sequences of two peptides demonstrating bioactivity. Reportedly, peptide 9 is detected in casein hydrolysates involved in nervous system development and antioxidant effects [ 36 , 37 ]. Peptide 12 is present in casein hydrolysates known to have antioxidant, anti-hypertension, and osteoblast proliferation/differentiation effects [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ha 46 studied the antioxidant peptides obtained from the hydrolysate of skim milk powders, and some of the peptides of the peptide having antioxidant activity potentially possessed antioxidant activity. In this experiment, the special DIQKVAGTWYSL, NENKVLVLDTDYKKY and CAQKKIIAEKTKIPAVF sequences found in the peptides of the top phase contained the WY, WYS, WYSL 43 , VAGTWY, VAGTWY, VAGTWYLS 47 , VLVLDTDYK 48 , KTKIPAVF 46 and IPAVF 48 peptides, which have antioxidant activity (Table 6 ). This may be another reason that the antioxidant activities of the peptides in the top phase were higher than those of the peptides in the bottom phase.…”
Section: Resultsmentioning
confidence: 99%